Election 2014 : why the republicans swept the midterms - Kilgore, Ed (EBL-Schweitzer, 2015)
How did the GOP trounce the Democrats in 2014? Acclaimed political analyst Ed Kilgore crunches the data, examines structural factors, places the vote in historical context, and reflects on implications for the 2016 presidential race in this bracing commentary on the recent Republican sweep.